Modelling variables that contribute to faculty willingness to collaborate with librarians: the case of the University Institute of Lisbon (ISCTE-IUL), Portugal - Amante, M. J.; Extremeño, A. I.; Costa, A. F. (Journal of Librarianship and Information Science, 2013)
This article discusses key variables that shape the willingness of faculty to work with librarians in higher education establishments. We use the Librarian-Library/Faculty Relationship Model to highlight the variables which faculty members consider to be the most relevant in that relationship. The article begins with a discussion of the causes of tensions between faculty and librarians. This is followed by a descriptive and co-relational study of the ISCTE-IUL University Institute of Lisbon library. The study uses qualitative and quantitative methods, namely a focus group and a survey. There was a good fit between the Librarian-Library/Faculty Relationship Model and the data (CMIN/DF=4.067), and the model explained 58% of the dependent variable, namely faculty willingness to collaborate with librarians. Our final model confirmed the relationships proposed in our initial model, and allowed us to identify a range of new relationships, which may contribute to a deeper understanding of the dynamics of different socio-cultural processes (included as variables in the model) affecting the relationship between faculty and librarians, so as to what factors shape the willingness of faculty to collaborate with librarians. The model shows that 14% of the willingness of faculty to collaborate with librarians can be attributed to key attributes of faculty, namely gender, age, department, academic qualification, professional category, and the length of career.